Process Parameter Optimization Of 3D Printer Using Response Surface Method - Nazan, Muhammad Afdhal; Ramli, Faiz Redza; Alkahari, Mohd Rizal; Sudin, Mohd Nizam; Abdullah, M. A. (Asian Research Publishing Network (ARPN), 2017)
The purpose of this paper is to minimize the warp deformation that usually occurs to plastic part produced by 3D printers. The process involved 3D solid modelling to design, 3D printing with coated adhesive applied on the printing platform, warping deformation measurement and statistical analysis. The optimization processes involved Design on Experiment (DOE) technique where Responses Surface Methodology (RSM) is applied by using Minitab software. The experiment produced the minimum result of warping deformation value when the layer temperature, infill density, first layer height and other layer height is 192°C, 13%, 0.20mm and 0.30mm respectively.